Physiochemical Processes to Reduce Friction and Wear Under Selective Transfer Conditions—A Review - Filip Ilie; Constantin-Daniel Cotici; Alina Juganaru (Lubricants)
A selective transfer is realized safely if the material pair and the lubricant are adequate, in the presence of a relative motion and an energy favoring the transfer. The paper highlights the mechanism of achieving the selective transfer phenomenon and analyzes the physiochemical aspects that take place in a suitably lubricated friction pair (here, bronze/steel lubricated with glycerin) that favor friction by reducing the friction force and implicitly reducing the wear in the selective transfer conditions. In addition, the paper seeks to highlight the effect that the servowitte layer (film) that appears on the friction pair surfaces following the selective dissolution of the superficial layer in the contact area has on the factors that influence the friction and wear process through the implications on the friction coefficient and the wear itself.